Technological investments and green energy production in Central and Eastern Europe - Marcin Salamaga (Entrepreneurial Business and Economics Review (EBER), 2025)
Objective: The article aims to examine the impact of technological investments on the development of wind energy and photovoltaics in Central and Eastern European countries (CEE) belonging to the EU. Research Design & Methods: In the analysis of the impact of expenditure on technical investments, I used panel threshold analysis and bootstrap simulation tests. I built the models based on the basis of annual data on the renewable energy market from 2013-2023 from the 'Our World in Data' databases and Eurostat. Findings: Research and development (R&D) expenditure stimulates the production of electricity from wind turbines to a greater extent than from PV panels. The strongest stimulation of electricity production simultaneously by a wind turbine and PV panels will occur when R&D expenditure ranges from 0.96% to 1.39% of GDP. If these expenses are in the range of 0.78% to 0.96% of GDP, solar energy will be stimulated the most, while if R&D expenditures are in the range of 1.39% to 1.61%, wind energy will be stimulated the most by these expenses. A simultaneous weakening of the development of wind and solar energy will occur when R&D expenditure is below 0.78% of GDP. Exceeding subsequent R&D expenditure thresholds weakens the effects of increasing energy production from renewable energy sources, which is caused by the intensification of the impact of various barriers inhibiting the development of renewable energy sources. Implications & Recommendations: The obtained results may be helpful for decision-makers responsible for shaping energy policy in individual countries of Central and Eastern Europe. Stimulation of the renewable energy sector through R&D expenditure is limited due to the existing barriers to the development of renewable energy sources specific to various countries. Fully exploiting the potential of renewable energy requires a gradual overcoming of these limitations. Energy policy aimed at eliminating barriers to the development of renewable energy should consider the local conditions of individual countries in terms of their natural conditions, available resources, energy infrastructure, diversification of energy sources, etc. Contribution & Value Added: The article presents an original analysis of the impact of expenditure on technological investments using panel threshold analysis and bootstrap simulation tests. The presented results bring added value to economic and policy research in the renewable energy sector.
Keywords: C38; Q42; Q55; 330; Central and Eastern Europe (CEE); panel threshold analysis; photovoltaics; renewable energy sources; wind energy